2021
DOI: 10.1177/1045389x211026381
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced frequency synchronization for concurrent aeroelastic and base vibratory energy harvesting using a softening nonlinear galloping energy harvester

Abstract: This paper proposes a softening nonlinear aeroelastic galloping energy harvester for enhanced energy harvesting from concurrent wind flow and base vibration. Traditional linear aeroelastic energy harvesters have poor performance with quasi-periodic oscillations when the base vibration frequency deviates from the aeroelastic frequency. The softening nonlinearity in the proposed harvester alters the self-excited galloping frequency and simultaneously extends the large-amplitude base-excited oscillation to a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 53 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…When the wind speed exceeds the critical wind speed, the piezoelectric and electromagnetic modules will work together. Chen et al 176 proposed a softened nonlinear aeroelastic dance energy harvester that harvests energy from wind and foundation vibrations. Karami et al 177 developed a new compact nonlinear piezoelectric wind harvester, a structure that stabilizes a piezoelectric biaxial by repelling magnetic forces.…”
Section: Application Of Energy Harvesting Technologymentioning
confidence: 99%
“…When the wind speed exceeds the critical wind speed, the piezoelectric and electromagnetic modules will work together. Chen et al 176 proposed a softened nonlinear aeroelastic dance energy harvester that harvests energy from wind and foundation vibrations. Karami et al 177 developed a new compact nonlinear piezoelectric wind harvester, a structure that stabilizes a piezoelectric biaxial by repelling magnetic forces.…”
Section: Application Of Energy Harvesting Technologymentioning
confidence: 99%
“…The experimental results demonstrated that the amplitude of voltage output increased by 53%, and the bandwidth achieved was ten times wider compared with the linear galloping harvester. Chen et al [34] presented a softening nonlinear aeroelastic galloping energy harvester for enhanced energy harvesting from concurrent wind flow and base vibration. The softening nonlinearity of the proposed harvester modulated the selfexcited galloping frequency and simultaneously enlarged the frequency range of the large-amplitude base-excited oscillation.…”
Section: Introductionmentioning
confidence: 99%